2007
DOI: 10.1162/jocn.2007.19.8.1316
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Attentional Selection Predicts Distractor Devaluation: Event-related Potential Evidence for a Direct Link between Attention and Emotion

Abstract: Links between attention and emotion were investigated by obtaining electrophysiological measures of attentional selectivity together with behavioural measures of affective evaluation. Participants were asked to rate faces that had just been presented as targets or distractors in a visual search task. Distractors were rated as less trustworthy than targets. To study the association between the efficiency of selective attention during visual search and subsequent emotional responses, the N2pc component was quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
70
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 17 publications
10
70
1
Order By: Relevance
“…In two experiments measuring social-emotional evaluation of faces, we found robust devaluation of stimuli sharing a feature that had just been ignored in a previous search task, thus replicating prior reports using similar stimuli (Goolsby et al, in press;Kiss et al, 2007). Our goal in the present study was to determine whether this distractor-devaluation effect would be dependent on visual WM.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In two experiments measuring social-emotional evaluation of faces, we found robust devaluation of stimuli sharing a feature that had just been ignored in a previous search task, thus replicating prior reports using similar stimuli (Goolsby et al, in press;Kiss et al, 2007). Our goal in the present study was to determine whether this distractor-devaluation effect would be dependent on visual WM.…”
Section: Discussionsupporting
confidence: 85%
“…When stimuli with these features are subsequently encountered, an inhibitory state is reinstantiated, leading to affective devaluation (Goolsby et al, in press). Other behavioral (Fenske, Raymond, & Kunar, 2004;Raymond, Fenske, & Westoby, 2005) and electrophysiological (Kiss et al, 2007) data support the notion that distractor devaluation is specifically mediated by inhibition applied to distractors. A key component of this theoretical view is that the inhibitory attentional state becomes associated in memory with the to-be-ignored feature (Tipper, Grison, & Kessler, 2003), a process that presumably requires visual working memory (WM) resources.…”
mentioning
confidence: 53%
“…This confirmed that the N2pc is sensitive to semantic relations between a distractor picture and the target being searched for in a multielement display. These results support Eimerʼs (1996) finding that the N2pc can be influenced by relatively high-level properties of a display (see also Eimer & Kiss, 2007;Kiss et al, 2007). In general, the N2pc amplitude was greater on trials where the target was present relative to when it was absent.…”
Section: Discussionsupporting
confidence: 83%
“…When the attention task required selection among two same-category items (e.g., houses) on the basis of a feature (e.g., a transparent overlay color), distractor devaluation was found for items from an unrelated category (faces) if they shared the previously ignored feature (overlay color). This and other behavioral (e.g., Fenske et al, 2005;Fenske, Raymond & Kunar, 2004), electrophysiological (Kiss et al, 2007), and neuroimaging (Doalla, Raymond, Shapiro, Eimer & Nobre, 2011) findings support the proposal that distractor devaluation results from task-specific attentional inhibition that becomes associated with the distracting feature. When this feature is presented later in the to-be-evaluated stimulus, inhibition becomes reinstantiated and modulates affective responses.…”
supporting
confidence: 80%